A systematic review of methods to assess intake of fruits and vegetables among healthy European adults and children: a DEDIPAC (DEterminants of DIet and Physical Activity) study. Issue 3 (14th September 2016) - Riordan, Fiona; Ryan, Kathleen; Perry, Ivan J; Schulze, Matthias B; Andersen, Lene Frost; Geelen, Anouk; van't Veer, Pieter; Eussen, Simone; Dagnelie, Pieter; Wijckmans-Duysens, Nicole; Harrington, Janas M
Abstract: Objective: Evidence suggests that health benefits are associated with consuming recommended amounts of fruits and vegetables (F&V), yet standardised assessment methods to measure F&V intake are lacking. The current review aims to identify methods to assess F&V intake among children and adults in pan-European studies and inform the development of the DEDIPAC (DEterminants of DIet and Physical Activity) toolbox of methods suitable for use in future European studies. Design: A literature search was conducted using three electronic databases and by hand-searching reference lists. English-language studies of any design which assessed F&V intake were included in the review. Setting: Studies involving two or more European countries were included in the review. Subjects: Healthy, free-living children or adults. Results: The review identified fifty-one pan-European studies which assessed F&V intake. The FFQ was the most commonly used ( n 42), followed by 24 h recall ( n 11) and diet records/diet history ( n 7). Differences existed between the identified methods; for example, the number of F&V items on the FFQ and whether potatoes/legumes were classified as vegetables. In total, eight validated instruments were identified which assessed F&V intake among adults, adolescents or children. Conclusions: The current review indicates that an agreed classification of F&V is needed in order to standardise intake data more effectively between European countries. Validated methods used in pan-European populations encompassing a range of European regions were identified. These methods should be considered for use by future studies focused on evaluating intake of F&V.